2012
DOI: 10.1158/1535-7163.mct-11-0535
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of Cancer Cells by KU-0060648, a Dual Inhibitor of DNA-PK and PI-3K

Abstract: DNA double-strand breaks (DSB) are the most cytotoxic lesions induced by topoisomerase II poisons. Nonhomologous end joining (NHEJ) is a major pathway for DSB repair and requires DNA-dependent protein kinase (DNA-PK) activity. DNA-PK catalytic subunit (DNA-PKcs) is structurally similar to PI-3K, which promotes cell survival and proliferation and is upregulated in many cancers. KU-0060648 is a dual inhibitor of DNA-PK and PI-3K in vitro. KU-0060648 was investigated in a panel of human breast and colon cancer ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 37 publications
3
98
0
1
Order By: Relevance
“…DNA-PK inhibitors NU7441and KU0060648 can be used to inhibit Akt activation [169171]. These inhibitors have been studied as anti-cancer agents.…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…DNA-PK inhibitors NU7441and KU0060648 can be used to inhibit Akt activation [169171]. These inhibitors have been studied as anti-cancer agents.…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…Furthermore, 14 was shown to potentiate not only IR in vitro but also DNA-inducing cytotoxic anticancer agents, both in vitro and in vivo. A counter-screen against other members of the PI3K PIKK family revealed that some of the compounds were potent mixed DNA-PK and PI3K inhibitors, including 14 [30,31]. The favourable biological activity of 14 was complemented by superior drug-like properties compared to NU7441 (13), and acceptable plasma protein binding, combined with weak activity against hERG and a panel of cytochrome P450 (CYP) drug-metabolising enzymes (Table 4) [30].…”
Section: (Scheme 4)mentioning
confidence: 99%
“…PI3K ve DNA-PK'nin ikili inhibitörü olan KU-0060648 etoposit ve doksorubisin birlikte kullanıldığında DNA-PKc olan hücrelerde sitotoksiteyi arttırırken, DNA-PKc olmayanlarda etkili olmamıştır. Bu bulgu DNA-PK inhibisyonunun sitotoksisitede önemli olduğunu göstermiştir [24]. görevi olduğunu da göstermektedir [31].…”
Section: Discussionunclassified